ERS International Congress, Madrid, 2019: highlights from the Allied Respiratory Professionals' Assembly. Issue 1 (6th April 2020) - Oliveira, Ana; Rutter, Matthew; Quijano-Campos, Juan Carlos; Herrero-Cortina, Beatriz; Clari, Marco; O'Rourke, Aoife; McGowan, Aisling; Burtin, Chris; Sajnic, Andreja; De Brandt, Jana
This article provides an overview of outstanding sessions that were (co)organised by the Allied Respiratory Professionals' Assembly during the European Respiratory Society International Congress 2019 in Madrid, Spain. Session content was mainly targeted at allied respiratory professionals such as respiratory physiologists, respiratory physiotherapists and respiratory nurses, and is summarised in this document. Short take-home messages related to pulmonary function testing highlight the importance of quality control. Furthermore, novel findings regarding the assessment of functional status call attention to bodily factors that can affect functional status. Regarding pulmonary rehabilitation, data were presented about the use of equipment and type of exercise training in COPD and lung cancer. Recent developments in physical activity-related research give insight in enablers of physical activity after hospital admission. The importance of integrated respiratory care was also highlighted, with the occupational therapist, nurse, and nutritional and psychological counsellor playing a pivotal role, which relates directly to research in the field of respiratory nursing that formulates the need for more nursing led-interventions in the future. To conclude, this review provides readers with valuable insight into some of the emerging and future areas affecting clinical practice of allied healthcare professionals. A highlights review of selected presentations from #ERSCongress 2019 by @ERS_Assembly9 http://bit.ly/2VNFgAj